(untitled) (Revista de Estudios Europeos, 2026)
Since independence, France has been the colonial power that has the mosts ties with its formers colonies in the Sahel Region. These ties are based on military, political or financyl agreements. However, they have been deteriorating in recent years especially after the failure of the Barkhane Operation, the military intervention that aims to stop the advance of terrorists. Accordingly, anti-french sentiment has surged ; there is the rupture of relationship, particularly at the political and military levels. Others powers have been moved into the region, which means a loss of franch influence.